2008
DOI: 10.1021/jm800876b
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Quinazolines as Histamine H4 Receptor Inverse Agonists Using a Scaffold Hopping Approach

Abstract: From a series of small fragments that was designed to probe the histamine H(4) receptor (H(4)R), we previously described quinoxaline-containing fragments that were grown into high affinity H(4)R ligands in a process that was guided by pharmacophore modeling. With a scaffold hopping exercise and using the same in silico models, we now report the identification and optimization of a series of quinazoline-containing H(4)R compounds. This approach led to the discovery of 6-chloro-N-(furan-3-ylmethyl)2-(4-methylpip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(120 citation statements)
references
References 28 publications
(97 reference statements)
1
118
0
1
Order By: Relevance
“…The hH 4 R ligands that display a clear bias toward ␀-arrestin2 recruitment can be divided into three structural groups: one quinoxaline (VIII, VUF10214) (Smits et al, 2008), one isothiourea (IV, VUF5223) , and four indolecarboxamides (VII, VUF10056, VUF6002, VUF11273, and VUF11012). These compounds are neutral antagonists or inverse agonists for G␣ i protein-dependent signaling but act as agonists in the ␀-arrestin2 recruitment assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hH 4 R ligands that display a clear bias toward ␀-arrestin2 recruitment can be divided into three structural groups: one quinoxaline (VIII, VUF10214) (Smits et al, 2008), one isothiourea (IV, VUF5223) , and four indolecarboxamides (VII, VUF10056, VUF6002, VUF11273, and VUF11012). These compounds are neutral antagonists or inverse agonists for G␣ i protein-dependent signaling but act as agonists in the ␀-arrestin2 recruitment assay.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, both industry and academia have discovered and characterized many new hH 4 R ligands, mainly on the basis of hH 4 R binding affinity and specificity (Jablonowski et al, 2003;Terzioglu et al, 2004;Thurmond et al, 2004;Lim et al, 2005Lim et al, , 2006Liu et al, 2008;Smits et al, 2008;Igel et al, 2009;Strakhova et al, 2009;Schneider et al, 2010;Smits et al, 2010). The therapeutic value of such hH 4 R ligands is potentially very interesting, not only for pathologies such as airway inflammation and allergic rhinitis but also for other inflammatory conditions (inflammatory bowel disease and atopic dermatitis) .…”
Section: Introductionmentioning
confidence: 99%
“…Inverse agonists stabilize the R state of GPCRs and reduce agonist-independent basal G-protein activity (Seifert and Wenzel-Seifert, 2002). Meanwhile, numerous H 4 R antagonists (Jablonowski et al, 2003;Terzioglu et al, 2004;Venable et al, 2005;Smits et al, 2008) and agonists (Hashimoto et al, 2003;Lim et al, 2005;Igel et al, 2009) have been identified. Although thioperamide is commonly used as the reference hH 4 R inverse agonist (Lim et al, 2005;Thurmond et al, 2008), the ligand is actually only a partial inverse agonist .…”
mentioning
confidence: 99%
“…These compounds were synthesized as per previously reported method. 24,26 In a 350 mL round pressure vial 16-18 g urea was heated at 150-155 C till it melted. To the liquid urea solution 0.1 eq.…”
Section: General Informationmentioning
confidence: 99%